GENE ACTION OF AGRONOMIC TRAITS IN RICE (Oryza sativa L.) - Biswas, P. S.; Haque, M. Enamul (Bangladesh Journal of Plant Breeding and Genetics, 2007)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;">Six parent diallel cross without reciprocal was studied to investigate the genetic behavior of different agronomic traits in rice. The analysis of Wr-Vr graph showed that panicle length, thousand grain weight and grain yield per plant did not follow the additive-dominance model indicating epistatic gene action responsible for the expression of these traits. All other traits under the study were conditioned by overdominance gene action except grains per panicle, which was controlled by partial dominance. The Yr?<span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"> (Vr + Wr)?<span style="font-size: 10.0pt; font-family: "Times New Roman","serif"; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;"> graph revealed random distribution of dominant and recessive gene in expressing different traits in different parent, while correlation between parental mean and parental order of dominance indicated increasing effect of dominant gene for all the traits except days to heading and % spikelet sterility. DOI: http://dx.doi.org/10.3329/bjpbg.v20i2.17033